Lorcaserin and phentermine exert anti-obesity effects with modulation of the gut microbiota - Song, Eun-Ji; Shin, Na Rae; Jeon, Songhee; Nam, Young-Do; Kim, Hojun (Frontiers in Microbiology, 2023)
Although drugs have been reported to modulate the gut microbiota, the effects of anti-obesity drugs on the gut microbiota remain unclear. Lorcaserin (LS) and phentermine (PT) are commonly used anti-obesity drugs. However, to our best knowledge, no studies have simultaneously assessed the effects of LS and PT on obesity and gut microbiota. This study aimed to explore the relationship between the anti-obesity effects of LS and PT and re-modulation of host gut microbiota. To test hypothesis, we fed C57BL/6J mice with a high-fat diet supplemented with LS and PT via oral gavage for eight weeks. After sacrifice, body weight, fat accumulation and serum biomarkers were measured, and the gut microbial composition was analyzed using 16s rRNA amplicon sequencing. LS and PT were observed to modulate the gut microbial composition and restore gut microbial dysbiosis, as indicated by an increased Firmicutes/Bacteroidetes ratio. Significantly modulated genera by LS and PT treatment were strongly correlated with obesity-related markers. Additionally, LS and PT increased the mRNA level of GPR120 in the colon tissue. ASV3566, which corresponds to Eubacterium coprostanoligenes, were correlate with GPR120 and obesity related markers such as GPT and TG. In conclusion, LS and PT can modulate the gut microbiota dysbiosis and the gut microbiota plays a role in mediating the anti-obesity effect of drugs.